Short Communication: The oleaginous Candida tropicalis isolated from mangrove soil in eastern Thailand and the fatty acid composition profile of its intracellular lipids - SUDARAT WONGCHAMREARN; PARIMA BOONTANOM; SUNISA UNGWIWATKUL; NANNAPHAT EMNIN; AIYA CHANTARASIRI (Society for Indonesian Biodiversity, 2023)
Abstract. Wongchamrearn S, Boontanom P, Ungwiwatkul S, Emnin N, Chantarasiri A. 2023. Short Communication: The oleaginous Candida tropicalis isolated from mangrove soil in eastern Thailand and the fatty acid composition profile of its intracellular lipids. Biodiversitas 24: 5088-5095. Oleaginous yeasts are microorganisms that can accumulate intracellular lipids at a rate of more than 20% of their cell dry weight. They are considered ideal microbes for a sustainable bioeconomy and a promising source for biotechnological applications. Thus, the exploration of efficient oleaginous yeasts from various environments is necessitated. At present, the number of oleaginous yeasts that have been discovered from mangrove environments remains scarce. Therefore, this study isolated and screened for lipid-accumulating yeast strains in mangrove soil samples collected from Rayong Province and Chonburi Province, Thailand. The intracellular lipids of isolated yeasts were extracted and quantitatively analyzed to evaluate the efficient oleaginous strains. Fifteen yeast strains were considered lipid-accumulating yeasts based on the Sudan IV staining method and lipid content determination, with intracellular lipid accumulation ranging from 5.71±1.89% (w/w) to 33.83±1.41% (w/w). The isolated yeast strain MJ13 was designated the most efficient oleaginous strain and subsequently genetically identified as Candida tropicalis. The fatty acid composition of its intracellular lipids was analyzed by gas chromatography, which consisted of five saturated fatty acids and five unsaturated fatty acids with 10-22 carbon atoms. The predominant fatty acids were palmitic (C16:0) and stearic (C18:0) acids. Some fatty acids essential to the human body and pharmacological sciences were detected, involving a-linolenic (C18:3n3) and cis-13,16-docosadienoic (C22:2) acids. This oleaginous yeast strain could be applied in lipid-related biofuel and high-value bioeconomy applications.